A new duet in cancer biology: AMPK the typical and UBE2O the atypical - Isabelle K. Vila; Su Jung Song; Min Sup Song (Molecular & Cellular Oncology, 2017)
Ubiquitin-conjugating enzyme E2O (UBE2O) is upregulated in human cancers. We have demonstrated that genetic deletion or pharmacological blockade of UBE2O reduces tumorigenesis through inhibiting the mammalian target of rapamycin complex 1–hypoxia-inducible factor 1-α pathway. Critically, UBE2O targets adenosine monophosphate (AMP)-activated protein kinase-α 2 (AMPKα2) for ubiquitination and degradation. We thus suggest the UBE2O-AMPKα2 axis as a potential therapeutic target for cancer.